The relationship between a microfinance-based healthcare delivery platform, health insurance coverage, health screenings, and disease management in rural Western Kenya - Molly Rosenberg; James Akiruga Amisi; Daria Szkwarko; Dan N. Tran; Becky Genberg; Maya Luetke; Sina Kianersi; Jane Namae; Jeremiah Laktabai; Sonak Pastakia (BMC Health Services Research, 2020)
Abstract Background Structural barriers often prevent rural Kenyans from receiving healthcare and diagnostic testing. The Bridging Income Generation through grouP Integrated Care (BIGPIC) Family intervention facilitates microfinance groups, provides health screenings and treatment, and delivers education about health insurance coverage to address some of these barriers. This study evaluated the association between participation in BIGPIC microfinance groups and health screening/disease management outcomes. Methods From November 2018 to March 2019, we interviewed a sample of 300 members of two rural communities in Western Kenya, 100 of whom were BIGPIC microfinance members. We queried participants about their experiences with health screening and disease management for HIV, diabetes, hypertension, tuberculosis, and cervical cancer. We used log-binomial regression models to estimate the association between microfinance membership and each health outcome, adjusting for key covariates. Results Microfinance members were more likely to be screened for most of the health conditions we queried, including those provided by BIGPIC [e.g. diabetes: aPR (95% CI): 3.46 (2.60, 4.60)] and those not provided [e.g. cervical cancer: aPR (95% CI): 2.43 (1.21, 4.86)]. Microfinance membership was not significantly associated with health insurance uptake and disease management outcomes. Conclusions In rural Kenya, a microfinance program integrated with healthcare delivery may be effective at increasing health screening. Interventions designed to thoughtfully and sustainably address structural barriers to healthcare will be critical to improving the health of those living in low-resource settings.